Deciphering past and present atmospheric metal pollution of urban environments: The role of black crusts formed on historical constructions. (10th January 2020) - García-Florentino, Cristina; Maguregui, Maite; Ciantelli, Chiara; Sardella, Alessandro; Bonazza, Alessandra; Queralt, Ignasi; Carrero, Jose Antonio; Natali, Claudio; Morillas, Héctor; Madariaga, Juan Manuel; Arana, Gorka
Abstract: Construction materials affected by black crusts (BCs) can be subjected to restoration, demolition, recycling or even to their management as waste products. Therefore, the determination of their chemical features should be considered a crucial step before undertaking any action. In this work, we present the development of an analytical methodology useful to be implemented as a routine screening tool to detect recent and past atmospheric emissions of heavy metals, nowadays superficially deposited or even encapsulated in BCs. For its development, BCs together with the underneath original substrate/construction material were sampled from the historical construction Punta Begoña Galleries (Getxo, Basque Country, North of Spain). In order to detect quickly and in a cost-effective way the stratification of the metallic deposits in the BCs over time (surface or external/recent and internal/past), thin sections were analyzed by elemental spectroscopic imaging techniques (SEM-EDS and μ-ED-XRF). In the external part of the BCs, iron particles were mainly identified, whereas in the inner areas (past deposition events) of the most exposed BCs to the atmosphere, lead accumulations together with zinc and copper were identified. Additional Raman imaging studies allowed to perform the molecular speciation study of lead, identifying mainly laurionite (PbClOH) together with hydrocerussite (Pb3 (CO3 )2 (OH)2 ). The presence of the mentioned lead chloride hydroxide confirms the role of the marine aerosol (chloride input) in the formation of the metallic compounds. These experimental evidences were used to assist the chemical equilibrium models developed to explain the reactivity pathway, which lead to the formation of the identified compounds. Through ICP-MS and lead isotopic ratio analysis, more than 3000 mg kg −1 of lead were quantified in the BCs, probably coming from the old emissions conducted by the old power station close to the construction, . That lead content can be high enough to consider those crusts as a source of metallic contamination and a possible risk to the environment and human health. Highlights: Black Crusts as information source of past/recent metals emissions to the atmosphere. Thin sections and spectroscopic imaging techniques to reveal past emission events. Rapid screening before applying more tedious methodologies (e.g. ICP-MS). Inner Pb accumulations coming from the emissions of a power station of the 60's. Oxidized Pb particles and Cl- (marine aerosol) reaction to form PbClOH (laureonite).